ANALISIS PENGARUH VARIABEL FUNDAMENTAL TERHADAP HARGA SAHAM SEKTOR INFRASTRUKTUR DAN SEKTOR ENERGI - Salsabil, Yafie Irsyad; Vietha Devia (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
The aim of this research is to provide evidence regarding the influence of fundamental factors, namely: Return on Equity, Debt to Equity Ratio, Current Ratio, Total Assets Turn Over, and Earning Per Share on stock prices both partially and simultaneously. This research was conducted on 6 infrastructure sector and energy sector companies listed on the Indonesia Stock Exchange in 2019-2023. The sampling technique is through the purposive sampling method. The statistical test tool used is a panel data regression model with partial t test output and simultaneous f test. The results of this research partially show that Debt to Equity Ratio and Earning Per Share have a significant effect on stock prices, while Return on Equity, Current Ratio and Total Assets Turn Over do not have a significant effect on stock prices. In simultaneous testing, all variables studied including Return on Equity, Debt to Equity Ratio, Current Ratio, Total Assets Turn Over, Earning Per Share have a significant effect on stock prices.